Morphology and crystallization behavior of PCL/SAN blends containing nanosilica with different surface properties. Issue 43 (20th July 2016) - Qian, Jing; Xiao, Zhilin; Dong, Lin; Tang, Dahang; Li, Mengjue; Yang, Qi; Huang, Yajiang; Liao, Xia
ABSTRACT: Morphology and crystallization behavior of poly(ɛ‐caprolactone) (PCL) in its 80/20 blends with poly(styrene‐co‐acrylonitrile) (SAN) containing hydrophobic or hydrophilic nanosilica was investigated. It was found that hydrophilic nanosilica displayed a more significant refinement effect on co‐continuous morphology of PCL/SAN blends than hydrophobic nanosilica for its selective distribution within the PCL matrix but closer to the two‐phase interface. Ring‐banded spherulites were observed in both kinds of nanosilica‐filled blends, the periodic distance of which decreased with increasing nanosilica content. Hydrophilic nanosilica reduced the dependence of the periodic distance of ring‐banded spherulites on the crystallization temperature more efficiently than hydrophobic nanosilica. Furthermore, crystallization process of PCL/SAN blends filled with hydrophobic nanosilica was suppressed as the restriction effect of nanosilica on the crystal growth always outweighed their heterogeneous nucleation effect. In contrast, low content of hydrophilic nanosilica (≤1 wt %) were more likely to exhibit growth restriction effect rather than nucleation effect, whereas heterogeneous nucleation effect of higher content of hydrophilic nanosilica (>1 wt %) dominated over growth restriction effect on facilitating the crystallization behavior. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44157. Abstract :